Spin carbon nanotubes into CNT fibers - Lim, Johnathan See Kwan. (2013)
This research is about the study of the mechanical properties of the Carbon NanoTubes (CNT) fibers that are being spun and twisted together. The spun single strand fibers are then followed by a liquid shrinking process to densify the fibers. After densifying, each strand of fiber were tested for their mechanical properties before they were divided into smaller segments and twisted together to form multi-ply fibers, ranging from a 2 ply CNT yarn to a 10 ply CNT yarn. Samples from the multi-ply fibers were then tested to investigate how the mechanical properties of the twisted fibers change with respect to the different pitch and number of fibers twisted together. Results showed that for a 2-ply and 3-ply CNT yarn, there is an optimal pitch value giving the optimal increase in its overall tensile stress by around 20%. Any pitch below the optimal value will starts to degrades the tensile stress until it reaches a negative value. Results for 4-ply and 6-ply CNT yarns also showed an increase in mechanical stress by 30% and 40%, respectively. It is believed that higher number multi-ply CNT yarns could actually lead to a higher increase in mechanical strength.